Respuesta :
-9x - 6 ≥ -3 (x - 4) ⇒ First, multiply out the -3(x -4)
-9x - 6 ≥ -3x + 12 ⇒ Then collect all the 'x' term on one side and the constants on the other side
-9x + 3x ≥ 12 + 6 ⇒ Then simplify the like term
-6x ≥ 18 ⇒ Divide both sides by -6
x ≥ -3 ⇒ This is the answer
-9x - 6 ≥ -3x + 12 ⇒ Then collect all the 'x' term on one side and the constants on the other side
-9x + 3x ≥ 12 + 6 ⇒ Then simplify the like term
-6x ≥ 18 ⇒ Divide both sides by -6
x ≥ -3 ⇒ This is the answer
Answer:
x ≥ -3
Step-by-step explanation:
i used a calculator, please give brainliest